Relations of the Spiritual Well-Being Questionnaire Domains with Other Areas of Well-Being: A Commentary Based on Existing Published Studies - Gomez, Rapson (Journal of religion and health, 2025)
The Spiritual Well-Being Questionnaire (SWBQ) measures the spiritual well-being domains of personal, communal, environmental, and transcendental well-being as proposed in Fisher's four-factor model of spiritual well-being. This commentary provides a critical overview of the literature on the associations of the SWBQ domains of spiritual well-being with other areas of general well-being. The commentary revealed consistent positive associations for the personal domain and, to a lesser degree, for the communal domain, with other areas of well-being. The associations for the environmental domain were rare, and the associations were often absent for the transcendental domain. On the basis of observations reported here, the personal domain in the SWBQ has the best concurrent/external validity in terms of relation with some aspects of general well-being, whereas the other domains have limited relevance.